Chronic renal failure-induced multiple-organ injury in rats is alleviated by the selective CysLT1 receptor antagonist montelukast - YEGEN, BERRAK; ERCAN, FERİHA; ŞENER, TARIK EMRE (ELSEVIER SCIENCE INC, 2007)
Chronic renal failure (CRF) is associated with oxidative stress that promotes production of reactive oxygen species and cytokine release. We aimed to investigate the possible protective effect of montelukast, a CysLT1 receptor antagonist, against oxidative damage in a rat model of CRF, induced by 5/6 reduction of renal mass. Male Wistar albino rats were randomly assigned to either the CRF group or the sham-operated control group, which received saline or montelukast (10 mg/kg, i.p.) for 4 weeks. At the end of the 4 weeks, rats were decapitated and trunk blood was collected. Creatinine, blood urea nitrogen and lactate dehydrogenase (LDH) activity were measured in the serum samples, while leukotriene B-4, TNF-alpha, IL-1 beta, IL-6, total antioxidant capacity (AOC) and leukocyte apoptosis were assayed in plasma samples. Kidney, lung, heart and brain tissue samples were taken for the determination of tissue malondialdehyde (MDA), glutathione (GSH) levels, and myeloperoxidase (MPO) activity. Oxidant-induced tissue fibrosis was determined by tissue collagen contents, and the extent of tissue injuries was analyzed microscopically. CRF caused significant decreases in tissue GSH and plasma AOC, which were accompanied with significant increases in MDA levels, MPO activities, and collagen contents of all the studied tissues, while the circulating levels of the pro-inflammatory mediators, LDH activity, creatinine and BUN were elevated. Montelukast treatment reversed all these biochemical indices, as well as histopathological alterations induced by CRF. Similarly, flow cytometric measurements revealed that leukocyte apoptosis was increased in CRF group, while montelukast reversed this effect. In conclusion, CRF-induced oxidative tissue injury occurs via the activation of pro-inflammatory mediators and by neutrophil infiltration into tissues, and that protective effects of montelukast on CRF-induced injury can be attributed to its ability to inhibit neutrophil infiltration and apoptosis, to balance oxidant-antioxidant status and to regulate the generation of pro- inflammatory mediators. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: chronic renal failure; leukotriene; inflammation; oxidative injury; ISCHEMIA-REPERFUSION INJURY; OXIDATIVE STRESS; SUPEROXIDE-DISMUTASE; LIPID-PEROXIDATION; INFLAMMATION; HEMODIALYSIS; LEUKOTRIENES; UREMIA; MYELOPEROXIDASE; GENERATION